Diversity of Trichoderma species associated with the black rot disease of Gastrodia elata, including four new species - Ye, Chuwen; You, Yanbo; Li, Wenjie; Jing, Tingting; Mo, Minghe; Qiao, Min; Yu, Zefen (Frontiers in Microbiology, 2024)
Introduction Trichoderma species establish symbiotic relationships with plants through both parasitic and mutualistic mechanisms. While some Trichoderma species act as plant pathogenic fungi, others utilize various strategies to protect and enhance plant growth. Methods Phylogenetic positions of new species of Trichoderma were determined through multi-gene analysis relying on the internal transcribed spacer (ITS) regions of the ribosomal DNA, the translation elongation factor 1-α (tef1-α) gene, and the RNA polymerase II (rpb2) gene. Additionally, pathogenicity experiments were conducted, and the aggressiveness of each isolate was evaluated based on the area of the cross-section of the infected site. Results In this study, 13 Trichoderma species, including 9 known species and 4 new species, namely, T. delicatum, T. robustum, T. perfasciculatum, and T. subulatum were isolated from the diseased tubers of Gastrodia elata in Yunnan, China. Among the known species, T. hamatum had the highest frequency. T. delicatum belonged to the Koningii clade. T. robustum and T. perfasciculatum were assigned to the Virens clade. T. subulatum emerged as a new member of the Spirale clade. Pathogenicity experiments were conducted on the new species T. robustum, T. delicatum, and T. perfasciculatum, as well as the known species T. hamatum, T. atroviride, and T. harzianum. The infective abilities of different Trichoderma species on G. elata varied, indicating that Trichoderma was a pathogenic fungus causing black rot disease in G. elata. Discussion This study provided the morphological characteristics of new species and discussed the morphological differences with phylogenetically proximate species, laying the foundation for research aimed at preventing and managing diseases that affect G. elata.